Effect of organic solvents on peroxidases from rice and horseradish: Prospects for enzyme based applications - Singh P.; Prakash R.; Shah K. (My University, 2025)
A feasibility test for rice peroxidase (RP) enzyme as a substitute for horseradish peroxidase (HRP) was carried out. The activity of HRP was maximum at 30 °C with pH 6.0-7.0. The purified rice peroxidase showed optimum activity at 30 °C with pH 7-8 and was thermostable till 68 °C, which is higher than the temperature reported for HRP. RP obeyed Michaelis-Menten kinetics. With increasing substrate concentrations, RP and HRP had Vmax as 8.23 μM min-1 and 4.21 μM min-1 and Km as 5.585 and 3.662 mM, respectively. In 10% 1,4-dioxane and ethanol, RP exhibited 2 and 1.3 times higher activity, respectively than HRP. Shelf life studies show RP to be significantly stable till 60 h in 20% 1,4-dioxane and till 12 h in ethanol. The activity of RP/HRP increased gradually with 0%-40% ethanol or 0%-30% 1,4-dioxane till 20 h with a sharp decline thereafter. The stability of HRP and RP reduced with increasing storage period. Enzyme efficiencies compared as Vm/Km showed water miscible organic solvents, viz.1,4-dioxane and ethanol, to exhibit a regular decrease in V m/Km with increase in organic solvent concentration whereas, a reverse trend was observed with water-immiscible solvent like chloroform. The relative activity of RP and HRP enzymes upon immobilization on poly-5-carboxy-indole shows increasing enzyme activity with time and with guaiacol/dopamine hydrochloride as substrates. Immobilized RP had a better relative activity with dopamine as substrate than immobilized HRP, whereas with guaiacol both RP and HRP had a comparable activity upon immobilization. Results suggest rice peroxidase to be a cheaper and convenient enzyme system for immobilization using organic solvents. The high thermal stability, more stability in organic solvents and longer shelf life of RP over the immobilizing matrix suggest conducting polyindole having carboxyl functional groups to be a suitable matrix for the covalent entrapment of rice peroxidase through amide linkage. Good sensitivity and fast response to dopamine makes RP a suitable enzyme system for monitoring dopamine levels in aqueous medium. © 2012 Elsevier B.V. All rights reserved.